Метод класифікації зображень з використанням принципу ближнього сусіда - Рибалка, М. О. (ХНУРЕ, 2021)
The work is devoted to the classification of images in computer vision systems according to the description of the set of descriptors of key points. Using the algorithm of the nearest neighbor, the classifier is implemented in a database of three etalons. A transformed image was fed to the input. The results of software modeling confirmed the efficiency of the method.
Keywords: комп'ютерний зір; ключова точка; розпізнавання образів